2008
DOI: 10.1007/s00442-008-1024-z
|View full text |Cite
|
Sign up to set email alerts
|

Population variation in plant traits associated with ant attraction and herbivory in Chamaecrista fasciculata (Fabaceae)

Abstract: The benefits of ant-plant-herbivore interactions for the plant depend on the abundance of ants and herbivores and the selective pressures these arthropods exert. In plants bearing extrafloral nectaries (EFN), different mean trait values may be selected for by different populations in response to local herbivore pressure, ultimately resulting in the evolution of differences in plant traits that attract ants as defensive agents against herbivory. To determine if variation in traits that mediate ant-plant interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 48 publications
3
46
0
1
Order By: Relevance
“…Overall, our results support the enemies hypothesis (Root 1973). Chamaecrista fasciculata may be acting as an ''insectary plant'' (Atsatt and Odowd 1976) for nearby Opuntia individuals by ''sharing'' the anti-herbivore effects of its EFN production and its well-documented attractiveness to predacious ants (Abdala-Roberts and Marquis 2007; Barton 1986;Kelly 1986;Rios et al 2008;Rutter and Rausher 2004). What is not clear from our study is whether this AR is due solely to differences in ant abundance, or also to differences in ant species assemblages, which we did not measure.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Overall, our results support the enemies hypothesis (Root 1973). Chamaecrista fasciculata may be acting as an ''insectary plant'' (Atsatt and Odowd 1976) for nearby Opuntia individuals by ''sharing'' the anti-herbivore effects of its EFN production and its well-documented attractiveness to predacious ants (Abdala-Roberts and Marquis 2007; Barton 1986;Kelly 1986;Rios et al 2008;Rutter and Rausher 2004). What is not clear from our study is whether this AR is due solely to differences in ant abundance, or also to differences in ant species assemblages, which we did not measure.…”
Section: Discussionsupporting
confidence: 82%
“…obsv.). At least 28 ant species have been recorded collecting EFN from C. fasciculata (Barton 1986;Boecklen 1984;Kelly 1986;Rios et al 2008;Stiles and Jones 2001); the vast majority of these species are found in the subfamilies Myrmicinae (14 species) or Formicinae (10 species). Two studies performed in northern Florida found the most common visiting ants to be Forelius (=Iridomyrmex) pruinosus, Camponotus floridanus, and Crematogaster ashmeadi (Barton 1986;Boecklen 1984).…”
Section: Ant Predation On An Invasive Herbivore 2263mentioning
confidence: 99%
“…We already know that within an EFN-bearing plant population the richness of associated ants differs among plants [13], [14], [15] One of the main factors explaining this intrapopulation variation is based on the difference in the reward offered (quantity and quality of nectar), where individuals with better rewards would be most visited by ants [16], [17]. On the other hand, nectar quantity and quality can vary along the day, and on the same plant [18], [19], [20], which means that an individual plant may be not considered to be a good resource throughout the day.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence of selection for increased EFN nectar production at peak periods of herbivore activity in Macaranga (Heil et al. 2000), in populations exposed to higher levels of herbivore damage in Chamaecrista fasciculata (Rios, Marquis & Flunker 2008), and for synchrony with peak ant activity periods in some Malpighiaceae (Pascal & Belin‐Depoux 1991). Additionally, there has been a clear shift to constitutive secretion in the myrmecophytic ant‐acacias where ants are always present (Heil et al.…”
Section: Introduction: Costs and Benefits Of Ants On Flowersmentioning
confidence: 99%